Controlling the excited-state dynamics of low band gap, near-infrared absorbers via proquinoidal unit electronic structural modulation. Issue 9 (19th June 2017) - Bai, Yusong; Rawson, Jeff; Roget, Sean A.; Olivier, Jean-Hubert; Lin, Jiaxing; Zhang, Peng; Beratan, David N.; Therien, Michael J.
Abstract : Modulating the extent of configuration interaction steers the excited-state relaxation pathways and dynamics of high oscillator strength NIR absorbers that exploit proquinoidal conjugation. Abstract : While the influence of proquinoidal character upon the linear absorption spectrum of low optical bandgap π-conjugated polymers and molecules is well understood, its impact upon excited-state relaxation pathways and dynamics remains obscure. We report the syntheses, electronic structural properties, and excited-state dynamics of a series of model highly conjugated near-infrared (NIR)-absorbing chromophores based on a (porphinato)metal(ii )-proquinoidal spacer-(porphinato)metal(ii ) (PM-Sp-PM ) structural motif. A combination of excited-state dynamical studies and time-dependent density functional theory calculations: (i) points to the cardinal role that excited-state configuration interaction (CI) plays in determining the magnitudes of S1 → S0 radiative ( k r ), S1 → T1 intersystem crossing ( k ISC ), and S1 → S0 internal conversion ( k IC ) rate constants in thesePM-Sp-PM chromophores, and (ii) suggests that a primary determinant of CI magnitude derives from the energetic alignment of thePM andSp fragment LUMOs (Δ E L ). These insights not only enable steering of excited-state relaxation dynamics of high oscillator strength NIR absorbers to realize either substantial fluorescence or long-lived triplets ( τ T1 > μs) generated at unit quantum yield ( Φ ISC = 100%), but also crafting of those having counter-intuitive properties: for example, while (porphinato)platinum compounds are well known to generate non-emissive triplet states ( Φ ISC = 100%) upon optical excitation at ambient temperature, diminishing the extent of excited-state CI in these systems realizes long-wavelength absorbing heavy-metal fluorophores. This work highlights approaches to: (i) modulate low-lying singlet excited-state lifetime over the picosecond-to-nanosecond time domain, (ii) achieve NIR fluorescence with quantum yields up to 25%, (iii) tune the magnitude of S1 –T1 ISC rate constant from 10 9 to 10 12 s −1 and (iv) realize T1 -state lifetimes that range from ∼0.1 to several μs, for these modelPM-Sp-PM chromophores, and renders new insights to evolve bespoke photophysical properties for low optical bandgap π-conjugated polymers and molecules based on proquinoidal conjugation motifs.